(untitled) (diségno, 2021)
Among the ‘unconventional’ graphic practices, around the middle of the last century, in the circles of avant-garde cinema, that of drawing directly on film, with the most diverse techniques, became widespread, making films in which figurative abstraction was often used. Among the most successful films of this genre, there is Begone Dull Care, a work by Norman McLaren made with the contribution of Evelyn Lambart, in which –with a distinctly visionary trait and using the most diverse techniques– an animation is built perfectly synchronized with music specially written by jazz pianist Oscar Peterson. After having taken into consideration the story of the making of the film, in the following note we examine the works McLaren refers to in order to build his graphic language, mature and surprising, and the different forms of connection that the author has established between music and the images, showing how in many cases these overcome the construction, albeit veiled, of any form of musical notation, thus avoiding the banal direct correspondence between sounds and images, pushing in the direction of the realization of completely visionary abstract image sequences.